Inherited and Acquired Determinants of Hepatic CYP3A Activity in Humans - Matthaei, Johannes; Bonat, Wagner Hugo; Kerb, Reinhold; Tzvetkov, Mladen Vassilev; Strube, Jakob; Brunke, Stefanie; Sachse-Seeboth, Cordula; Sehrt, Daniel; Hofmann, Ute; von Bornemann Hjelmborg, Jacob; Schwab, Matthias; Brockmöller, Jürgen (Frontiers in Genetics, 2020)
Human CYP3A enzymes (including CYP3A4 and CYP4A5) metabolize about 40% of all drugs and numerous other environmental and endogenous substances. CYP3A activity is highly variable within and between humans. As a consequence, therapy with standard doses often results in too low or too high blood and tissue concentrations resulting in therapeutic failure or dose-related adverse reactions. It is an unanswered question how much of the big interindividual variation in CYP3A activity is caused by genetic or by environmental factors. This question can be answered by the twin study approach. Using midazolam as CYP3A probe drug, we studied 43 monozygotic and 14 dizygotic twins and measured midazolam and its metabolite 1-OH-midazolam. In addition, endogenous biomarkers of CYP3A activity, 4ß-OH-cholesterol and 6ß-OH-cortisol, were analyzed. Additive genetic effects accounted for only 15% of the variation in midazolam AUC, whereas 48% was attributed to common environmental factors. In contrast, 73, 56, and 31% of 1-OH-midazolam, 4ß-OH-cholesterol and 6ß-OH-cortisol variation was due to genetic effects. There was a low phenotypic correlation between the four CYP3A biomarkers. Only between midazolam and its 1-OH-metabolite, and between midazolam and 6ß-OH-cortisol we found significant bivariate genetic correlations. Midazolam AUC differed depending on the CYP3A4∗22 variant (p = 0.001) whereas plasma 4ß-OH-cholesterol was significantly lower in homozygous carriers of CYP3A5∗3 (p = 0.02). Apparently, non-genomic factors played a dominant role in the inter-individual variation of the CYP3A probe drug midazolam. A small intra-individual pharmacokinetic variation after repeated administration of midazolam was rated earlier as indication of high heritability of CYP3A activity, but according to present data that could also largely be due to constant environmental factors and/or heritability of liver blood flow. The higher heritabilities of 4ß-OH-cholesterol and of 1-OH-midazolam may deserve further research on the underlying factors beyond CYP3A genes. Clinical Trial Registration:ClinicalTrials.gov: NCT01845194 and EUDRA-CT: 2008-006223-31.